The Role of Emerging ICT in the Ports: Increasing Utilities According to Shared Decisions - Russo, Francesco; Musolino, Giuseppe (Frontiers in Future Transportation, 2021)
Geographical location, infrastructures and services are the main consolidated pillars of a port, in terms of its capacity to compete, and to cooperate, with other ports. In the last years a new pillar can be identified: the emerging technologies. Ports’ issues were initially solved with individual ICT solutions adopted by each decision-maker, which generated efficiencies in the three main port flows: cargo, information, and financial. However, new benefits and challenges are connected with the introduction of shared emerging ICT technologies among decision-makers inside ports. The crucial issue concerns the fact that several decision-makers could share a decision about a single port operation. Therefore, the effectiveness and efficiency of ports depend on how the interactions between the decision-makers are solved. Port operations are associated to movements (cargo) and transactions (information and financial) in a synchronic graph, that allows to highlight the role of emerging technologies in the modification of port operation generalized cost, considering the different decision makers. The focal point concerns the building of a theoretical model using the formal equations of Transport System Models) (TSMs), (for the estimation of the cost for a Unit of Load (UL, e.g. a container) travelling along a path, composed by a sequence of port operations, inside a port with and without emerging technologies. The theoretical model proposed provides the possibility to estimate ex-ante the reduction of cost (port time of UL) given by the introduction of a new technologies and of a Port Community System (PCS). Different scenarios, considering some cases, ranging from the absence of ICT to the presence of a PCS, are compared and considering the different situations from a non-congested port to the congested one. The noventy of the study concerns on the one hand the extension of TSMs to port systems, highlighting the problem of a non-single decision maker (two or more) in some port operations, and on the other hand the possibility of reducing the generalized cost (e.g. time) in the same operations in which there are concurrent decision makers, through the use of an advanced PCS. The numerical example reported confirms the theoretical results.